A Comparison of Electronic and Paper Versions of the Montreal Cognitive Assessment. (July 2019) - Wallace, Sarah E.; Donoso Brown, Elena V.; Simpson, Richard C.; D'Acunto, Kristin; Kranjec, Alexander; Rodgers, Mackenzie; Agostino, Caroline
Abstract : Objective: The objective of this study was to investigate older adults' performance on the paper and electronic Montreal Cognitive Assessment (eMoCA). Design: Repeated measures and correlational design. Participants: A convenience sample of 40 adults over 65 years of age living in the community. Interventions: Participants completed the eMoCA and paper Montreal Cognitive Assessment (MoCA) in a randomized order during 1 session. Participants reported their touchscreen experience and comfort and indicated their modality preferences. Main Outcome Measures: The primary outcome measures were paper MoCA and eMoCA total and subscale scores. Secondary outcome measures included participants' reported touchscreen experience and comfort, as well as post-administration preferences. Results: A moderate statistically significant correlation was found between eMoCA and paper MoCA performance across all participants. Analysis comparing first administration modality only (eMoCA vs. paper MoCA) found no statistically significant difference in total scores; however, there was a statistically significant difference for the visuospatial/executive subscale, which required physical interaction with paper or the tablet. For this subscale, participants scored lower on the eMoCA versus paper MoCA. There was a statistically significant correlation between experience with touchscreen devices and performance on the eMoCA, but not between modality preference and performance. Conclusion: Modality of administration can affect performance on cognitive assessments. Clinicians should consider individuals' level of touchscreen experience before selecting administration modality. Abstract : Supplemental Digital Content is available in the text.